Seasonal Changes in an Afromontane Forest Bird Community in Tanzania - Dinesen, Lars; Lehmberg, Thomas; Romdal, Tom S.; Sonne, Jesper; Hansen, Louis A. (Frontiers in Ecology and Evolution, 2022)
Seasonal variation in the composition of avian communities is poorly documented in African montane forests. Using field observations, mist-netting data (63,424 NMH), recording of mixed-species flocks (160 flocks noted), and of the feeding ecology of greenbuls (757 observations), we document marked seasonal changes in a bird community in an East African montane forest (1,340-2,130 m) in the Udzungwa Mountains in south-central Tanzania. This mountain range contains the largest remaining forests in the Eastern Arc Mountains in Tanzania, part of a key global biodiversity hotspot. Our analysis is based on data in the wet and the dry season from about 14-man months of fieldwork. Field observation data combined with mist-net data demonstrate noticeable seasonal changes in certain species' abundances, indicating seasonal movements out of the montane forest during the dry season and movements of part of the populations for other species. Our mist-net results show significant difference in species abundances between the two seasons driven by 16 species. We also document significant changes in diet for two species of greenbuls, which shift feeding behaviour from arthropods in the wet season to include a larger proportion of fruit in their dry season diet. Our results further show that birds are more active in mixed-species flocks in the dry season, with significantly higher average number of species and of individuals in the dry season i.e. 11.3 (+- 0.52 SE) species, 32.3 (+- 1.76 SE) individuals] compared to the wet season 9.7 (+- 0.78 SE) species, 20.8 (+- 1.85 SE) individuals].. One of two very distinctive types of mixed-species flocks - confined to the understory - exists only in the dry season. We discuss these changes to seasonal variability in climate, i.e. temperature and precipitation.